Vitamin D Deficiency in 7 - 11 Year Old Children in Eastern Iran - Mahmoud Zardast; Kokab Namakin; Gholamreza Sharifzade; Mohamad Reza Rezvani; Yeganeh Rahmani; Shirin Behrozifar (International Journal of School Health, 2015)
Background: Vitamin D deficiency is a health problem in different countries. Vitamin D deficiency is an important health problem in both developed and developing countries. Recent reports on extra skeletal effects of vitamin D have led to increased interest in prevalence studies on states of deficiency/insufficiency of vitamin D. Objectives: The aim of this study was to determine the prevalence of vitamin D deficiency in children in city of Birjand, east of Iran. Patients and Methods: This cross-sectional study was carried out in winter of 2012 and comprised 238 students of primary schools aged between 7 and 11 years. Sampling was done through randomized multiple stage method. The data were obtained using a questionnaire consisting of questions about weight, height and serum level 25 (OH) vitamin D. Serum level 25 (OH) D < 20 ng/mL was defined as deficient, level 20 - 30 ng/mL as insufficient and the level > 30 ng/mL as sufficient. Results: Of the total number of 238 children surveyed, 110 (46.2%) were males and 128 (54.8%) females. Vitamin D levels in the subjects ranged from a minimum of 4.3 to a maximum of 63.1 ng/dL, with mean value of 15.4 ± 8.1 ng/dL. The deficient, insufficient and sufficient levels of vitamin D were found in 76.9%, 18.5%, and 4.6% of the students, respectively. Moreover, vitamin D deficiency was significantly higher in the females. Conclusions: In regard to the protective role of vitamin D in preventing many chronic diseases, immediate intervention in the form of nutritional supplement is needed to overcome the high prevalence of vitamin D deficiency in children.